1513. Medically Attended Respiratory Syncytial Virus Hospitalizations (RSVH) and All-Cause Bronchiolitis Hospitalizations (BH) Among Children Aged ≤ 24 Months at RSV Season Start With Higher-Risk Congenital Heart Disease (CHD) Before and After the 2014 American Academy of Pediatrics (AAP) Policy. (31st December 2020) - Fergie, Jaime; Gonzales, Tara; Suh, Mina; Jiang, Xiaohui; Fryzek, Jon; Howard, Ashley; Bloomfield, Adam
Abstract: Background: In 2014, the AAP stopped recommending palivizumab for use in children with hemodynamically significant CHD (hs-CHD) aged 12 to 24 months at the RSV season start. This analysis investigates the impact of the 2014 AAP policy on the contemporary burden of RSVH and BH in children with CHD for whom palivizumab immunoprophylaxis is no longer recommended. Methods: All children with CHD aged ≤ 24 months at the start of the RSV season and hospitalized for RSV or BH during the 2010-2017 RSV seasons (November-March) were studied. RSVH and BH were defined by International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) and ICD-10-CM codes. As there are no ICD codes for hs-CHD, we evaluated the effect of the guidance on higher-risk CHD as defined by ICD codes. 1 Frequency and characteristics of RSVH and BH and disease severity (including intensive care unit [ICU] admission and mechincal ventilation) for these children before and after the 2014 AAP guidance using the Children's Hospital Association's Pediatric Health Information System ® (PHIS) data set were described. SAS version 9.4 was used for statistical analysis of this data, with z-tests method used to determine statistical significance. Results: RSVH significantly increased after 2014 for all higher-risk CHD children aged ≤ 24 months (3.4% [1992 RSVH CHD/59, 217 RSVH] before the 2014 guidance and 4.0% [1798 RSVH CHD/45, 470 RSVH] after; P < 0.0001) and for the subgroup of children aged 12 to 24 months at the start of the RSV season (0.5% before the guidance and 0.8% after; P < 0.0001). Disease severity as measured by ICU admissions in the 12 to 24 months subgroup also significantly increased after the 2014 guidance (0.2% before the guidance and 0.3% after; P < 0.0001). Mechanical ventilation usage was not statistically significantly increased after the 2014 guidance ( P =0.188). A similar pattern of results was found for BH. Conclusion: RSVH, BH, and associated disease severity significantly increased among higher-risk CHD children aged 12 to 24 months, within the PHIS health system, after the 3 RSV seasons following the 2014 AAP RSV immunoprophylaxis recommendations. Disclosures: Jaime Fergie, MD, AstraZeneca (Speaker's Bureau)Sobi, Inc. (Speaker's Bureau) Tara Gonzales, MD, Sobi, Inc. (Employee) Mina Suh, MPH, International Health, EpidStrategies (Employee) Xiaohui Jiang, MS, EpidStrategies (Employee) Jon Fryzek, PhD, MPH, EpidStrategies (Employee) Adam Bloomfield, MD, FAAP, Sobi, Inc. (Employee)